2020
DOI: 10.3389/fncel.2020.577912
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Modulation of Glial Function During Aging and Chronic Neuroinflammation

Abstract: Aging is a complex biological process that increases the risk of age-related cognitive degenerative diseases such as dementia, including Alzheimer's disease (AD), Lewy Body Dementia (LBD), and mild cognitive impairment (MCI). Even non-pathological aging of the brain can involve chronic oxidative and inflammatory stress, which disrupts the communication and balance between the brain and the immune system. There has been an increasingly strong connection found between chronic neuroinflammation and impaired memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 356 publications
2
60
0
Order By: Relevance
“…They also regulate the maturation of neurons and help maintain their function [ 147 , 148 ]. They are found in various states of activation and can be neuroprotective (reducing inflammation and stimulating repair) or neurotoxic (promoting inflammation that may result in neurodegeneration) [ 149 , 150 ]. They respond to inflammatory molecules such as cytokines and chemokines and are able to detect aggregated proteins such as Aβ [ 148 , 151 , 152 ].…”
Section: Mediators Of Neuroinflammationmentioning
confidence: 99%
“…They also regulate the maturation of neurons and help maintain their function [ 147 , 148 ]. They are found in various states of activation and can be neuroprotective (reducing inflammation and stimulating repair) or neurotoxic (promoting inflammation that may result in neurodegeneration) [ 149 , 150 ]. They respond to inflammatory molecules such as cytokines and chemokines and are able to detect aggregated proteins such as Aβ [ 148 , 151 , 152 ].…”
Section: Mediators Of Neuroinflammationmentioning
confidence: 99%
“…Levels of IL-6 in plasma were determined using BD OptEIA Mouse IL-6 ELISA according to the manufacturer’s instructions (BD Biosciences, San Jose, CA, USA), as previously described [ 33 ]. Briefly, 96-well plates were coated with anti-mouse IL-6 capture antibody at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, evidence of the anti-inflammatory role of α7 nAChR has also been addressed in vivo, were activation of the receptor showed protective effect in a model of chronic stress via inhibition of TLR4 and microglial activity [ 31 ]. All together, these findings point at α7 nAChR as an interesting target for neuroprotection, reviewed in [ 32 , 33 ]. Thus, in this study, we aim to evaluate how central α7 nAChR signaling controls the microglial response upon LPS peripheral challenge in adult and aged animals.…”
Section: Introductionmentioning
confidence: 99%
“…Early differentiation of MCI due to AD is crucial since early therapeutic intervention is indicated to be beneficial at least in slowing disease progression (Vellas et al, 2007;Molinuevo et al, 2011). It should be noted, though, that the etiology of MCI is heterogeneous, meaning that approximately half of the patients convert to dementia other than AD, or do not convert at all (Rowe et al, 2010;Bennett et al, 2012;Frisoni et al, 2017). Therefore, whether FDG PET has discriminative and predictive ability for MCI patients is of great clinical relevance.…”
Section: Patientsmentioning
confidence: 99%
“…PET imaging studies with tracers for both pre- and post-synaptic cholinergic targets have confirmed the abnormalities of cholinergic transmission in vivo , in AD, as manifested in altered levels of AChE, VAChT, and α 4 β 2 and α 7 nAChR's, and their correlations with Aβ deposition and cognitive functions. The α 7 nAChR is a target gaining increasing focus in recent years, due to its newly discovered participation in preventing amyloid toxicity and tau hyper-phosphorylation, in increasing synaptic strength and stability, and in modulating neuroinflammation by acting on non-neuronal cells (Wang et al, 2003 ; Conejero-Goldberg et al, 2008 ; Halff et al, 2014 ; de Oliveira et al, 2016 ; Maurer and Williams, 2017 ; Gamage et al, 2020 ). Renewed interests have also been seen in the mAChR, especially the M1 and M4 subtypes, for therapeutic development for AD (Levey, 1996 ; Schliebs and Arendt, 2011 ; Melancon et al, 2013 ).…”
Section: Pet Tracers For Imaging Targets In the Cholinergic Systemmentioning
confidence: 99%